EFFICACY OF NEBIVOLOL IN TREATMENT OF WOMEN WITH CORONARY HEART DISEASE - N. A. Koryagina; A. V. Petrishcheva (Российский кардиологический журнал, 2014)
Aim. Evaluation of clinical efficacy and tolerability of beta-blockers in premenopausal women with stable angina.Material and methods. The anaysis of 43-55 years old premenopausal 50 women with stable angina was performed. Therapy included enalapril 2,5-10 mg daily, betaadrenoblocker in 1 group (23 persons) – 5-10 mg of bisoprolol daily, and in 2 group (27 pers.) nebivolol 2,5-5 mg daily (Nebilet®, “Berlin-Chemie/A. Menarini”, Germany), acetylsalycilic acid 100 mg daily during 6 months. The studies done were veloergometry, long-lasting ECG monitoring, echocardiography and also the test with reactive hyperemia on brachial artery. Severity of anxiety-depressive syndrome was evaluated usin hospital scale of anxiety and depression, and the severity of climacteric disorders – by the M. Kuppermann index.Results. With the therapy all patients self-reported improvement of their condition: in 80% there was a decrease of angina functional class, more significant in the second group. Also there was decrease of climacteric symptoms salience as anxiety-depressive disorders, especially in nebivolol group. By the results of ECG monitoring, i. e. frequency of rhythm dosirders (supraventricular and ventricular arrhythmias) there was lower quantity of episodes, more significant in nebivolol group. All groups showed an increase of basal brachial artery diameter, more significant in the 2nd group. Also we marked the changes in central hemodynamics parameters and sctructure-functional parameters of the left ventricle in both groups. Conclusion. Nebilet® in saily dose as 2,5-5 mg is an effective antianginal drug in women with CHD and stable angina pectoris. Under Nebilet® action there is improvement of systolic and diastolic functions of the left ventricle myocardium. With Nebilet® women with stable angina significantly increase exercise tolerance and there is a decrease of climacteric and anxiety-depressive syndrome.